2019
DOI: 10.1002/adma.201904040
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Nanoengineering: A Match Made for Precision Therapeutics

Abstract: Intense efforts from both scientists and physicians across Australia have been devoted onward advancing studies to fill the gap in understanding the biology and pathogenesis underlying cancer development. Exosomes are membrane-bound bio-nanoparticles secreted or released by most cells into the extracellular space. There has been an increasing interest in such bio-nanoparticles over the past 10 years, evident from the publication number of only 324 papers in 2006 to a massive increase to 4603 publications in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(123 citation statements)
references
References 87 publications
1
121
0
1
Order By: Relevance
“…Exosomes are also a promising type of novel drug delivery vehicle because of their ability to cross the BBB and shield their cargo from enzymatic and chemical degradation. Recent developments regarding nanoengineering using targeted exosomes for therapeutic purposes have been conducted by researchers, for example, Xin et al (2013b), Tran et al (2019).…”
Section: Exosomes As Novel Ad Therapeuticsmentioning
confidence: 99%
“…Exosomes are also a promising type of novel drug delivery vehicle because of their ability to cross the BBB and shield their cargo from enzymatic and chemical degradation. Recent developments regarding nanoengineering using targeted exosomes for therapeutic purposes have been conducted by researchers, for example, Xin et al (2013b), Tran et al (2019).…”
Section: Exosomes As Novel Ad Therapeuticsmentioning
confidence: 99%
“…As a novel therapeutic approach, drugs transmitted by exosomes has entered the preclinical research phase (85). In recent years, exosome-related nanovesicles have been used to the precise treatment of diseases (86)(87)(88).…”
Section: Exosome Uptake and Functionmentioning
confidence: 99%
“…Considering the targeted delivery function of exosomes, cell biology, pharmaceutical science, and nanotechnology are attracted to the new era of human-derived nanovesicles. Aptamer-mediated drug delivery system is considered to be a prominent therapeutic for nanodelivery (87). For example, after fusing with anti-epithelial cell adhesion molecule cancer (EpCAM), aptamer could carry transferrin/aptamer across blood-brain barrier to cure brain diseases (153).…”
Section: Prospects Of Exosome-derived Lncrnasmentioning
confidence: 99%
“…On account of their good stability, long circulating half-life and relatively good bio-safety, EVs are considered to be potential drug delivery systems with high delivery efficiency and low toxicity [252]. Moreover, studies have also shown that EVs have a unique "homing" ability (the capability to target the cell type similar to their source cells) [252,253]. Studies have shown that EVs actively target a specific cell type through a variety of mechanisms especially receptor-ligand recognition [254], and thus, by engineering EVs loaded with specific ligands (including antibodies, peptides, and aptamers) onto their surfaces, the targeting ability of EVs can be changed so that they target the cells that need them for functional intervention on specific cells [255,256].…”
Section: Discussion and Outlookmentioning
confidence: 99%